MODEL PEMBELAJARAN EFEKTIF DI ERA NEW NORMAL - Alfrid Sentosa; Dedy Norsandi (JURNAL PENDIDIKAN, 2022)
This article was created with the aim of providing an overview of how face-to-face learning in the new normal era, what kind of learning models can be applied by teachers in facing the challenges of education in the new normal era. The writing of this article uses the Literature Review method. The learning model is an important item in learning. Teachers as people who play an important role in the learning process must apply appropriate learning models so that learning objectives can be achieved. Several learning models that can be applied in the new normal era include: 1) Inquiry Learning Model, 2) Contextual Learning Model, 3) Expository Expository Learning Model, 4) Problem Based Learning Model, 5) Cooperative Learning Model, 6) PAIKEM learning model , 7) Quantum Learning Model, 8) Integrated Learning Model, 9) Multigrade learning Model, 10) Structured Task Learning Model, 11) Learning Portfolio Model, 12) Thematic Learning Model.